Otvoreni pristup naučnim informacijama / Open Access to Scientific Information (Pregled: časopis za društvena pitanja / Periodical for social issues, 2023)
Open access implies the idea of scientific information dissemination over the Internet that is free to the end user. The higher education and university libraries’ mission is to connect people and information, and the goals of open access help librarians respond to users' information queries more quickly. This paper presents the basic concepts of open access with an emphasis on creating an open access journal through ten steps. The open access portal at the University of Sarajevo is also presented within the paper, as well.
Keywords: open access; scientific information; open access journals; libraries; librarians